Decontextualized Instruction or Disembodied Reading?: Performance Context and Speech Performance in Proverbs - Currier, Elizabeth (Vetus Testamentum, 2024)
Scholars agree that the book of Proverbs cannot be related to an actual performance context. Many identify literarily staged performance contexts and, therefore, speech performances in the book. The idea of an actual performance context is dismissed on the ground that no oral-performance setting can be reconstructed for any part of Proverbs. In this article, I suggest that cognitive research into how humans process language fills theoretical lacunae in approaches that limit performance context and speech performance to ancient oral settings. I propose conceptual models of performance context and speech performance that account for interpretations common among scholars that Proverbs was produced to influence readers, in spite of our inability to reconstruct ancient oral performance settings. In sum, I suggest that the communicative (if asynchronous) interaction between producers and readers (ancient to modern) can be seen as the actual (if composite and entirely cognitive) performance context of the book.